Determinant Analysis and Effect of Variables on Work Life Balance of PSPCL Employees - Sondhi, Er. Surinder Paul (International Journal of Psychosocial Rehabilitation, 2020)
Work life balance is an equilibrium to manage work life and personal life which helps to provide balance in one’s life. To achieve spiritual development and happiness, individuals should work according to his/her own needs. So this concept helps to manage personal and professional life for better career. The present study focuses on factors as well as effects of imbalance due to changing environment, more ambitions and demands and so on. The study also includes solutions to make balance and accordingly generate benefits to organization and individuals. An organization can get better productivity by making new and favorable policies, through seminars and workshops, vacations and by providing flexible working hours. This balance will help an individual to generate creativity because stress free environment is important for creativity. So this study put light on negative impact of imbalanced work life and also positive impact of work life balance.